An experimental study of loads on a Formula SAE chassis using strain gauges and a low-cost data logger - Cestari, Mario Finato [UNESP] (Universidade Estadual Paulista (Unesp), 2024)
In a complete engineering project, the validation process is of great importance, as it is the phase where you can analyze the results of all the others. In a Formula SAE team, where the main objective is learning through hands-on xperience, this value should be even stronger. FSAE Brazil currently emphasizes this, requiring it during the design presentation. unfortunately, the Fênix Racing Team has faced many troubles with the validation process, mainly due to a lack of materials, reliance on third parties, and unpredictability of the schedule. This work aims to address this issue by developing a low-cost data logger using an Arduino board, a data logger shield, an HX711 module, and a complete Wheatstone bridge of strain gauges. The initial idea was to test this system on the car chassis, but that was not possible. The system was tested on a cantilever beam, calibrated with a series of static loads using known weig'hts, and tested with an impact and a pendulum system, both simulating dynamic loads. The system performed well in the second case, with an error of less than one percent. The results are very promising and could serve as a starting point for a more effective validation phase within the team.

O processo de validação desempenha grande importância na competude de um projeto de engenharia, pois é a fase em os resultados de todas as outras etapas são analisados. Em uma equipe de Formula SAE, onde o principal objetivo é o aprendizado atravéz de experiências práticas, esse princípio deve receber ainda mais destaque. Atualmente a competição Formula SAE Brasil se alinha com esse ideal, exigindo a presença da etapa de validação durante a apresentação da prova de design. Infelizmente a equipe Fênix Racing tem enfrentado muitas dificuldades noprocesso de validação, principalmente devido à falta de equipamentos, dependência de terceiros e imprevisibilidade do cronograma. Este trabalho tem como objetivo abordar esse problema desenvolvendo um sistema de aquisição de dados de baixo custo, utilizando uma placa Arduino, uma shield de data logger, um módulo HX711 e uma ponte completa de Wheatstone de extensômetros. A ideia inicial era testar este sistema no chassi do carro, mas isso não foi possível. O sistema foi testado em uma viga em balanço, calibrado com uma série de cargas estáticas utilizando pesos conhecidos, e testado com um impacto e um sistema de pêndulo, ambos simulando cargas dinâmicas. O sistema apresentou bom desempenho no segundo caso, com erro inferior a um por cento. Os resultados são muito promissores e podem servir como ponto de partida para uma fase de validação mais eficaz dentro da equipe.
Um estudo experimetal das cargas em um chassi de Formula SAE usando extensômetros e data logger de baixo custo
Keywords: Validation; Data logger; Strain gauge; Low-cost; Formula SAE; Chassis